Induction of Rat Germ Cell Apoptosis by Testosterone Undecanoate and Depot Medroxyprogesterone Acetate and Correlation of Apoptotic Cells with Sperm Concentration - Syafruddin Ilyas; Silvia W Lestari; Nukman Moeloek; Asmarinah Asmarinah; Siregar C Siregar (Acta Medica Indonesiana, 2016)
Aim: to investigate the safety and effectiveness of dose TU+DMPA hormones in developing potential male contraceptives. Methods: suppression of rat sperm concentration through increased apoptotic germ cells by in vivo administration of a long-acting androgen composed of a combination of testosterone undecanoate (TU) and depot medroxyprogesterone acetate (DMPA) was performed. Adult Sprague-Dawley rats received 2.5 mg TU every 6 week and 1.25 mg DMPA every 12 week for 60 week, a regimen known to rapidly reduce testosterone production by the testes and produce azoospermia within 12 week. Sperm concentration data were log transformed before analysis. Results are expressed as the mean±SEM. ANOVA, followed by post hoc test was used to determine differences across time and phase. T test was employed to determine differences between two groups. Results: apoptosis revealed significant increase in apoptotic germ cells (80% when rats were administered with TU+DMPA. Apoptotic germ cells can be found in several spermatogonia (20%), spermatocytes (30%), and spermatids (50%). Conclusion: dose TU+DMPA hormones may be a safe and effective way to develop potential male contraceptives.